Anticonvulsant drugs for generalized tonic-clonic epilepsy. (13th June 2017) - Coppola, Giangennaro; Piccorossi, Alessandra; Operto, Francesca Felicia; Verrotti, Alberto
ABSTRACT: Introduction : Primary generalized tonic clonic seizures (pGTCS) are still linked to major concerns for the clinic and hazards for patients suffering from idiopathic generalized epilepsy (IGE), so a quick search of the most effective and appropriate therapy is needed to control them. The key criteria for proper treatment are syndromic diagnosis and distinction between newly diagnosed and refractory patients. Other criteria include age, gender and comorbidities. Areas covered : Treatment for pGTCS has expanded in the last two years, with new antiepileptic drugs like perampanel joining valproic acid, lamotrigine, levetiracetam, topiramate, while further evidence-based data are required for zonisamide and lacosamide. Expert opinion : Currently, valproic acid can be considered as a first choice in male or menopausal women, and in the absence of weight issue, both in adults and in children, and in the absence of side effects such as insomnia and headache. Today, valproic acid is not recommended in child-bearing age and in relation to possible cognitive problems, especially in children. Lamotrigine and levetiracetam can be a viable alternative as a first choice. Topiramate is also effective as a first choice, but concerns may arise from its potential cognitive and memory adverse side effects. Additionally, perampanel and lacosamide are promising treatments.